Faktor Risiko yang Berpengaruh terhadap Kejadian Kanker Payudara di RSUP DR. Kariadi Semarang - Cici Priyatin; Elisa Ulfiana; Sri Sumarni (JURNAL KEBIDANAN, 2013)
Breast cancer is a disease where there is excessive growth or uncontrolled growth of cells (tissue) breast. Incidence of breast cancer increases if there are risk factors for breast cancer. In the last three years, breast cancer cases in Central Java increased. The incidence of breast cancer is high in Hospital Dr. Kariadi as many as 3925 cases in 2011 and 439 cases in 2012. This study aims to determine the major risk factors that affect the risks of breast cancer incidence in Dr. Kariadi Semarang in 2013. This research is analytic study with case control study approach. Population of this research were 248 breast cancer patients, with a sample of 76 respondents. The sample was women with breast cancer and treated in the gynecology department of Dr. Kariadi Hospital. However, the control group is women of childbearing age who do not have breast cancer and treated in Dr. Kariadi during July until August 2013. The data was gained from the medical record at Dr Kariadi Hopital. The data was analysed by Univariate analysis test and test selection. The results showed that the greater risk of menache age was 2,638, the first age of pregnancy was 1,694, parity amounted to 4.535, 2.118 was history of breastfeeding, duration of hormonal contraceptive use was 0.576, 6.938 for family history risk. It can be concluded that the most influential risk factors for breast cancer is family history. Women who have a family history of breast cancer has risks 6,938 times higher to develop breast cancer than women who have not a family history of breast cancer. It is suggested that preventive efforts should be made, to increase public awareness for the more active for early detection of breast cancer (BSE) so that the incidence of breast cancer can be treated as early as possible.